2021
DOI: 10.5376/pgt.2021.12.0002
|View full text |Cite
|
Sign up to set email alerts
|

SNP Identification from RAD-Seq Data in Faba Bean (<i>Vicia faba</i> L.)

Abstract: Faba bean is an important edible legume crop in China. Due to its huge genome size and no available reference genome, SNP marker is very limited in faba bean. To identify genome-wide SNP markers, we obtained 35.47 Gb data from eight landraces by RAD-sequencing, with an average of 4.77 Gb data for each accession. A total of 245443516 reads were generated, the single accession has an average of 30680439.5 reads, and the average length of the reads reaches to 144 bp. The Q20 and Q30 values were over 97.89% and 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It is noteworthy that, in the current scientific literature, the only case study in which RADseq technology is used for genotyping Cichorium species is the work of Patella et al, in which endive accessions were analysed using RADseq to identify the genes responsible for leaf shape in this crop [ 45 ]. Moreover, germplasm characterisation and population genetics studies based on RADseq genotyping have been performed, which showed the potential of this tool in other crop plants, such as peanut [ 46 ] and faba bean [ 47 ], as well as in other non-plant organisms. An example of this is represented in Sunde et al, where a comparison between codominant PCR-based microsatellite and RADseq is also provided [ 48 ], highlighting the higher informativeness of the GBS approach compared to conventional PCR.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, in the current scientific literature, the only case study in which RADseq technology is used for genotyping Cichorium species is the work of Patella et al, in which endive accessions were analysed using RADseq to identify the genes responsible for leaf shape in this crop [ 45 ]. Moreover, germplasm characterisation and population genetics studies based on RADseq genotyping have been performed, which showed the potential of this tool in other crop plants, such as peanut [ 46 ] and faba bean [ 47 ], as well as in other non-plant organisms. An example of this is represented in Sunde et al, where a comparison between codominant PCR-based microsatellite and RADseq is also provided [ 48 ], highlighting the higher informativeness of the GBS approach compared to conventional PCR.…”
Section: Discussionmentioning
confidence: 99%